Rhinosporidiosis in Sri Lanka: An overview - SN Arseculeratne (Anuradhapura Clinical Society, 2013)
Rhinosporidiosis, an enigmatic disease, is present in 90 countries world-wide. Sri Lanka has the highest prevalence per capita, while India has the largest number of reported cases. It is now appearing in Europe. Since its discovery in 1892, unresolved enigmas of the disease and its causative pathogen, still remain. This overview highlights these enigmas to encourage Sri Lankan researchers to investigate them.